2008
DOI: 10.1152/ajpendo.00026.2008
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic ethanol consumption differentially impact pathways limiting hepatic protein synthesis

Abstract: This review identifies the various pathways responsible for modulating hepatic protein synthesis following acute and chronic alcohol intoxication and describes the mechanism(s) responsible for these changes. Alcohol intoxication induces a defect in global protein synthetic rates that is localized to impaired translation of mRNA at the level of peptide-chain initiation. Translation initiation is regulated at two steps: formation of the 43S preinitiation complex [controlled by eukaryotic initiation factors 2 (eI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…29 In light of these findings, we set out to examine the mechanistic underpinnings of ethanol-induced down-regulation of signaling in the mTOR pathway. Chronically exposing lymphoma cell lines at levels readily attainable in human plasma (0-0.092 g/dL, or Ïł3 drinks per day maximally) 6 resulted in decreased phosphorylation of key downstream proteins involved in mTOR pathway signaling, including mTOR, p70 S6 kinase, RPS6, and 4E-BP1 (Figures 1,3B). Importantly, these levels of ethanol do not significantly impinge on cell viability ( Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29 In light of these findings, we set out to examine the mechanistic underpinnings of ethanol-induced down-regulation of signaling in the mTOR pathway. Chronically exposing lymphoma cell lines at levels readily attainable in human plasma (0-0.092 g/dL, or Ïł3 drinks per day maximally) 6 resulted in decreased phosphorylation of key downstream proteins involved in mTOR pathway signaling, including mTOR, p70 S6 kinase, RPS6, and 4E-BP1 (Figures 1,3B). Importantly, these levels of ethanol do not significantly impinge on cell viability ( Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that mice can consume water containing up to 20% ethanol without showing an aversion to the ethanol. 6,7 All control mice were pair-fed with the ethanol consuming groups to ensure nutritional intake was similar among groups. SUDHL-4 cells (10 6 ) were resuspended in 100 L phosphate-buffered saline and then mixed with an equal volume of Matrigel.…”
Section: In Vivo Tumor Growth In the Xenograft Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Among these tissues, the liver is the major site of alcohol-induced damage because it directly receives blood containing high concentrations of alcohol and is the major organ of ethanol metabolism, producing toxic metabolites from alcohol. 3 Liver injury due to ethanol exposure is mediated by two well-characterized pathways. 4 The first pathway involves alcohol oxidation by alcohol dehydrogenase and aldehyde dehydrogenase.…”
Section: Introductionmentioning
confidence: 99%